On Jordan-Hölder Theorem under Intuitionistic Fuzzy Groups (European Journal of Pure and Applied Mathematics, 2025)
The theory of intuitionistic fuzzy groups is an algebraic structure derivable from the utilization of groups in intuitionistic fuzzy sets. Many notions in group theory have been presented in intuitionistic fuzzy group theory. However, concepts like simple group, maximal normal subgroup, normal series, composition series, and the Jordan-Hölder Theorem are open problems in intuitionistic fuzzy group theory. Hence, this paper defines simple intuitionistic fuzzy groups, maximal normal intuitionistic fuzzy subgroups, normal series for intuitionistic fuzzy groups, and composition series for intuitionistic fuzzy groups with illustrations. In addition, the Jordan-Hölder Theorem in intuitionistic fuzzy group theory is verified. It is shown that every intuitionistic fuzzy group of a finite group possesses a composition series, and any two composition series for an intuitionistic fuzzy group of a finite group are equivalent.
Keywords: ntuitionistic fuzzy groups; Intuitionistic fuzzy subgroups; simple intuitionistic fuzzy groups; normal series for intuitionistic fuzzy groups; composition series for intuitionistic fuzzy groups